REFINEMENT OF THE POWERS OF LOCAL GOVERNMENT IN THE SPHERE OF EDUCATION MANAGEMENT - Saharuk O.P. (Pressing Problems of Public Administration, 2015)
The analysis of powers of local authorities in the management of education has been done.Features of the distribution of functions and powers in the educational sphere between localgovernments and local administrations. have been allocated. The basic directions of the furtherdevelopment of education policy at the local level have been designated.